RHODE ISLAND ANNUAL ACTION PLAN FOR YEAR ONE IMPLEMENTATION OF THE AMERICAN STOP SMOKING INTERVENTION STUDY FOR CANCER PREVENTION (Tufts Archival Research Center, 2007)
Report on Rhode Island Annual Action Plan for year one implementation of the American Stop Smoking intervention study for cancer prevention. Provides background on plan. Discusses clean indoor air in worksites and public places, purchase of cigarettes by minors, tobacco advertisement restriction, media advocacy, and efforts to maximize the accesibility of cessation and counselling services.